The management of intra-articular lateral femoral condyle (Hoffa) fracture of the knee using arthroscopy-assisted fixation: a case report - Aryana, I. G. N. Wien; Wibowo, Trimanto (International Journal of Research in Medical Sciences, 2018)
A Hoffa fracture is a type of supracondylar distal femoral fracture with fracture line located in the coronal plane. It is a rare injury consisting of tangential (coronal shear) fracture of distal femoral condyles. Unicondylar knee fractures are rare and present some diagnostic difficulties due to poor visibility on standard X-ray and are especially harder to identify in non-displaced fracture. A fifty-four-year-old male presented to our emergency room with a chief complaint of pain over his right knee that started 10 months prior. He previously was involved in a motor vehicle accident and underwent open reduction and internal fixation with plate and screws. Physical examination revealed swelling and tenderness over the right knee with limited range of motion. Plain X-ray showed union of tibia plateau fracture with plate and screws and no evidence of distal femoral fracture. A magnetic resonance imaging of the right knee was performed and revealed an intraarticular lateral condyle femur fracture with transverse configuration that was previously missed on plain X-ray. Arthroscopy-assisted reduction and internal fixation using antero-posterior and postero-anterior oriented screws were performed and good reduction was achieved. Diagnosis of this type of fracture is challenging and require some experience. Awareness of such entity and strong clinical suspicion are essential for diagnosis because most of the time the standard X-rays may appear normal. Arthroscopy-assisted fracture fixation using antero-posterior and postero-anterior oriented screws for Hoffa fracture offers many advantages and allows for early mobilization postoperatively without any loss of reduction.